FACTORS RELATED TO BEHAVIOR CHANGES STOP OPEN DEFECATION IN THE TALISAYAN RIVER COMMUNITY: Indonesia - Noor Aini, Luthfi; Suhelmi, Reni; Hansen, (HIGIENE: Jurnal Kesehatan Lingkungan, 2023)
Sanitation is an effort to prevent the emergence of environmental-based diseases. One of the pillars of STBM that needs to be followed up is pillar 1 regarding stopping open defecation. Communities along the Talisayan River in Berau Regency are still found practicing open defecation. This research was conducted to determine the relationship between education level, income level, knowledge of open defecation, the role of counseling from health workers, and socio-cultural aspects with the behavior of stopping open defecation on the banks of the Talisayan River. Analytical research with using a cross-sectional approach. Sampling used in this study is the method Simple Random Sampling with the head of the family as the respondent who lives on the banks of the Talisayan River totaling 112. Data was collected using a questionnaire then data in analysis using SPSS with univariate and bivariate analysis. The results showed that variable knowledge, socio-cultural aspects, and the role of counseling health workers have a significant relationship with behavior to stop open defecation with a p value smaller than 0.05, namely 0.000 each. Variable education level and income level do not have a significant relationship with behavior to stop open defecation with a p value greater than 0.05, namely 0.676 and 0.475. Variables of knowledge, socio-culture, and the role of counseling health workers have a significant relationship with open defecation, while education level and income level do not have a significant relationship with open defecation behavior in the communities along the Talisayan River. The culture of gotong royong needs to be maintained and developed in the community and the role of health educators to be further enhanced to increase awareness and positive behavior of the residents along the Talisayan River. Keywords : behavior to stop open defecation, socio-culture, socio-culture and counseling by health workers.